Controlling Oxygen-Based Electrochemical Reactions through Spin Orientation - Bhattacharjee, Satadeep; Lee, Seung-Cheol (American Chemical Society, 2018)
The role of spin orientation on the reactivity of oxygen reduction reaction (ORR) intermediates (O, OH) on a ferromagnetic electrode surface is studied using constrained density functional theory formalism. We show that the strength of the binding of these reaction intermediates depend on their relative spin orientations with respect to the magnetization of the electrode. This suggests that oxygen-based electrochemical reactions on ferromagnetic catalyst surfaces can be controlled through the applied magnetic field. In the present study, we demonstrate such a possibility through the study of an oxygen reduction reaction on a PdFe (001) surface by introducing a new concept: spin orientation dependent overpotential. Also, we have explained the origin of lower dissociation barrier for the O-2, molecule on ferromagnetic surfaces when its spin moment is antiparallel to the surface magnetization as reported in the recent experiments.
Keywords: PT-M M; REDUCTION ACTIVITY; 1ST PRINCIPLES; CO; ELECTROCATALYSTS; PERFORMANCE; CATALYSTS; DESIGN; NI; MAGNETISM